FIGURATIVE LANGUAGE ANALYSIS IN DISNEY SONGS - Nurcitrawati, Vera; Kareviati, Evie; Atmawidjaja, Nai (PROJECT (Professional Journal of English Education), 2019)
This research is titled "Figurative Language Analysis In Disney Song". The background of this research is to understand the use of figurative language contained in Disney song lyrics from the films Frozen and Tangled (Rapunzel). The objectives of this research are: (1) What types of figurative language are contained in the song, (2) figurative language functions contained in the song lyrics, and (3) what implicit meanings are contained in the lyrics of the song. The method used in this research is qualitative descriptive in observation, collecting data and conclusions from the research. The results of this study indicate that there are 5 types of figurative languages used in the lyrics of the two songs including idioms, hyperbole, personification, simile and alliteration.